2023
DOI: 10.3389/fspor.2023.1269870
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and injury prevention strategies for overuse injuries in adult climbers: a systematic review

Andrew Quarmby,
Martin Zhang,
Moritz Geisler
et al.

Abstract: IntroductionClimbing is an increasingly popular activity and imposes specific physiological demands on the human body, which results in unique injury presentations. Of particular concern are overuse injuries (non-traumatic injuries). These injuries tend to present in the upper body and might be preventable with adequate knowledge of risk factors which could inform about injury prevention strategies. Research in this area has recently emerged but has yet to be synthesized comprehensively. Therefore, the aim of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Previous research on chronic injuries in climbing typically includes small selections of participants with a wide range of methods and often of poor quality. 23 As the methods vary, it is not easy to compare results. Still, the present study indicates that the anticipated shift in the epidemiology of climbing injuries is ongoing.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research on chronic injuries in climbing typically includes small selections of participants with a wide range of methods and often of poor quality. 23 As the methods vary, it is not easy to compare results. Still, the present study indicates that the anticipated shift in the epidemiology of climbing injuries is ongoing.…”
Section: Limitationsmentioning
confidence: 99%
“…To avoid injuries, it is vital to know the most common injuries at different performance levels and for each gender. 23 It has previously been suggested that the epidemiology of injuries would change due to the change in the design of routes and boulders. 20 Still, we do not know what the change in movement pattern and the increased level of performance means for the distribution of injuries across the genders.…”
Section: Introductionmentioning
confidence: 99%